Analysis of the Causes and Countermeasures of Low Passenger Flow Effect of Tram Lines in China. Issue 1 (October 2020) - Xu, Zhengliang; He, Liying
Abstract: The development of modern tram in China is very rapid while the passenger flow effects of many existing tram lines are not as good as expected. In order to find out the main causes and countermeasures, this paper compares the passenger flow effects of 49 tram lines at home and abroad by indicator named passenger flow intensity. Then the impacts of land exploitative intensity of nearby regions, average distance between stations and traffic conditions of the same corridor on passenger flow effect are analyzed based on specific cases. Suggestions of strengthening land exploitative intensity of regions along the tram line, shortening the average distance between stations, avoiding setting tram line on the corridor where road traffic is not heavy or there are multiple parallel rail transit lines are finally made to improve pass enger flow effect of tram line.